Factors Affecting the Occurrence of Filariasis in East Lampung, Indonesia - Erisya Damayanti; Endang Budiati; Sugeng Eko Irianto; Atikah Adyas; Dian Utama Pratiwi Putri (Health Dynamics, 2025)
Background: East Lampung is an endemic area for filariasis. Survey results since 2004, showing Sekampung and Sekampung Udik sub-districts, indicate a microfilaria rate of filariasis above 1%. In 2024, 11 chronic filariasis patients were found. This research aims to analyze the influence of living habits, mosquito breeding sites, family support, the role of health workers, and the role of community leaders on the incidence of filariasis. Methods: This research type is quantitative with a case-control design. The research sample consisted of 44 respondents. The sampling technique used was purposive sampling. Data collection methods included interviews and observations using questionnaires and observation sheets as guidelines. Data analysis consisted of univariate, bivariate, and multivariate analyses. Results: Bivariate analysis showed the influence of living habits (p-value 0.043), mosquito breeding sites (p-value 0.004), family support (p-value 0.035), the role of health workers (p-value 0.027), and the role of community leaders (p-value 0.019) on the incidence of filariasis. Multivariate analysis revealed that living habits dominantly influence the incidence of filariasis with a p-value of 0.011. Conclusions: There is an influence of lifestyle habits on the incidence of filariasis, mosquito breeding, family support, the role of health workers, the role of community leaders on the incidence of filariasis in East Lampung Regency with the most influential variable, namely lifestyle habits, which dominantly affect the incidence of filariasis in East Lampung Regency.